Kinesiology of the musculoskeletal system foundations for rehabilitation - Neumann, Donald A. (Elsevier, 2017)
With its focus on the normal and abnormal mechanical interactions between the muscles and joints of the body, this comprehensive, research-based core text provides a foundation for the practice of physical rehabilitation. It presents kinesiology as it relates to physical rehabilitation in a clinically relevant and accessible manner-and acts as a bridge between basic science and clinical management